Factors associated with reported need of weight loss support among adults with overweight or obesity: results from a cross-sectional population study in 2022 in Sweden - Anu Molarius; Jan Karlsson (Cambridge University Press, 2024)
Abstract Objective: The aim of this study was to investigate factors associated with reported need of weight loss support among adults with overweight or obesity in the general population. Design: A cross-sectional population study based on a survey questionnaire sent to a random population sample. Multivariate odds ratios for reported need of weight loss support were calculated for socio-economic, lifestyle and health indicators, in total and by gender and age group. Setting: Five counties in Sweden in 2022. Participants: The study includes 10 069 persons with overweight or obesity (BMI ≥ 25 kg/m2) aged 30-69 years. BMI was based on self-reported weight and height. Results: In total, about 20 % reported needing weight loss support. The factors most strongly associated with reported need of weight loss support were obesity and female gender. Lack of social support, economic difficulties, physical inactivity, poor self-rated health, musculoskeletal pain and depression were also associated with reported need of weight loss support, whereas diabetes and hypertension were not. Some differences in these associations were observed between age groups. Conclusion: Reported need of weight loss support is more common among women than among men and associated with obesity, lack of social support, economic difficulties, physical inactivity, poor self-rated health, musculoskeletal pain and depression in both genders. These factors are important for planning preventive and weight-control measures among adults with overweight or obesity.